Ultralow thermal conductivity of beta-Cu2Se by atomic fluidity and structure distortion - Kim, Hyoungchul; Ballikaya, Sedat; Chi, Hang; Ahn, Jae-Pyung; Ahn, Kiyong; Uher, Ctirad; Kaviany, Massoud (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
We demonstrate a prototype thermal evolution path for liquid thermal conductivity in solids. Thermal evolution of beta-Cu2Se shows large interstitial displacement of constituent atoms marked by glass-like transitions and an asymptotic liquid thermal transport. Using ab initio molecular dynamics (AIMD), we identify these transitions, and confirm them with in situ transmission electron microscopy and electron energy loss spectroscopy. The thermal disorder of the Cu+ ions forms homopolar Cu-Cu bonds under a rigid Se framework, and at yet higher temperatures the Se framework undergoes thermal distortion. The non-equilibrium AIMD prediction of lattice thermal conductivity shows significant suppression of the phonon transport, in agreement with experiments and molecular behavior. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: THERMOELECTRIC PERFORMANCE; ELECTRON